Thermodynamic Study of Chitosan as a Corrosion Inhibitor for Carbon Steel in Chloride Solutions (NaCl and HCl) at Various Temperatures and Concentrations - Khafid Ubay Ilyas; Eni Budiyati; Nur Hidayati; Tri Widayatno (Jurnal Kimia Sains dan Aplikasi, 2024)
This research investigates the thermodynamic characteristics of chitosan as a corrosion inhibitor for carbon steel in chloride electrolyte environments, specifically saturated sodium chloride and 1 M hydrochloric acid, across different temperatures and concentrations. The study aimed to evaluate the effectiveness of chitosan in preventing corrosion and to examine the thermodynamic characteristics of the adsorption process. The results revealed that chitosan achieved the highest inhibition efficiency of 90.07% in a 1 M hydrochloric acid solution with a concentration of 250 mg/L at 303.15 K. In contrast, the maximum inhibition efficiency in a saturated sodium chloride solution was 50.50% at the same concentration of 250 mg/L and 303.15 K. Thermodynamic analysis showed that the adsorption of chitosan is spontaneous and exothermic in both media. The standard free energy of adsorption was found to be -38.63 kJ/mol at 303.15 K, decreasing to -43.69 kJ/mol at 343.15 K in saturated NaCl, and -42.40 kJ/mol at 303.15 K, decreasing to -48.65 kJ/mol at 343.15 K in 1 M HCl. The enthalpy of adsorption was -0.24976 kJ/mol in NaCl and 4.93560 kJ/mol in HCl, while the entropy of adsorption was -0.12661 J/mol·K in NaCl and -0.15610 J/mol·K in HCl. Additionally, the activation energy for corrosion increased from 1.61 kJ/mol at 0 mg/L to 6.96 kJ/mol at 250 mg/L chitosan in NaCl and from 4.10 kJ/mol at 0 mg/L to 23.79 kJ/mol at 250 mg/L chitosan in HCl. SEM analysis confirms the formation of a protective chitosan film, significantly reducing corrosion damage compared to uninhibited conditions. These findings indicate that chitosan is a highly effective corrosion inhibitor with favorable thermodynamic characteristics for applications in chloride-containing environments.